Energy-efficient Façade Design of Residential Buildings – An Innovative BIM-based Generative Design Approach - Ma, Wei (Curtin University, 2024)
The research develops and validates an innovative AI-aided approach integrating generative design (GD) with building information modelling (BIM) to generate integral and compliant energy-efficient residential façade designs automatically and efficiently. Guided by Pragmatism and structured by Design Research Methodology (DRM), the study addresses four objectives across four publications. The research advances AI-aided, energy-efficient building design, and the GD-BIM approach enhances design efficiency, supporting sustainable practices in architecture.